(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article analyzes the nature of poetic images in the work of Ravshan Fayz, one of the brightest representatives of modern Uzbek poetry. Based on the poet’s collection "In the Endless Hills of the Heart", the features of the creation of images through internal mental state, aesthetic formation and symbolic expression are highlighted. During the analysis, the semantic layers of images, their harmony with form and style, and the principles of using the poetic energy of the word are revealed. The author’s lyrics, through such symbols as heart, hill, window, autumn, reveal the inner experiences of a person, spiritual suffering, and a unique poetic approach to artistic thinking, are analyzed from a scientific and theoretical point of view.